2016
DOI: 10.1016/j.tiv.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyl exposure alters the expression profile of microRNAs associated with vascular diseases

Abstract: Exposure to persistent organic pollutants, including polychlorinated biphenyls (PCBs) is correlated with multiple vascular complications including endothelial cell dysfunction and atherosclerosis. PCB-induced activation of the vasculature subsequently leads to oxidative stress and induction of pro-inflammatory cytokines and adhesion proteins. Gene expression of these cytokines/proteins is known to be regulated by small, endogenous oligonucleotides known as microRNAs that interact with messenger RNA. MicroRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 44 publications
(49 reference statements)
0
27
0
Order By: Relevance
“…Lastly, it is also known that PCBs induce NF-jB activation that can lead to significant increase in inflammatory agent mRNA and protein expression (Eske et al 2014). In vitro and in vivo studies showed that POPs (which could include PCBs) trigger secretion of pro-inflammatory cytokines and alter lymphocyte functionin part, via disruption of T-cell receptor (TCR) signaling and cytokine production (Imbeault et al 2012;Wahlang et al 2016;Rousselet et al 2017). In many cases, induced increases in local levels of inflammatory agents (including cytokines such as tumor necrosis factor [TNF]-a, interferon [IFN]-c, interleukin [IL]-1b and IL-2, and reactive intermediates generated by local immune cells, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it is also known that PCBs induce NF-jB activation that can lead to significant increase in inflammatory agent mRNA and protein expression (Eske et al 2014). In vitro and in vivo studies showed that POPs (which could include PCBs) trigger secretion of pro-inflammatory cytokines and alter lymphocyte functionin part, via disruption of T-cell receptor (TCR) signaling and cytokine production (Imbeault et al 2012;Wahlang et al 2016;Rousselet et al 2017). In many cases, induced increases in local levels of inflammatory agents (including cytokines such as tumor necrosis factor [TNF]-a, interferon [IFN]-c, interleukin [IL]-1b and IL-2, and reactive intermediates generated by local immune cells, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…However, data on which miRNAs are affected after exposure to environmental chemicals, such as PCBs, are still scarce. To date only two studies have looked at the effect of PCBs on miRNA expression profiles; Zhu et al (2012) demonstrated differential expression of miRNAs in PCB exposed P19 cells in cardiac myocytes, and Wahlang et al (2016) have found that PCBs alter the expression profile of miRNAs associated with vascular disease. No studies have yet determined the effect of PCBs on any immune associated miRNAs, including miR‐155.…”
mentioning
confidence: 99%
“…It has been consistently demonstrated that exposure to environmental pollutants can influence epigenetic modifications (6569). Specifically, exposure to persistent organic pollutants can alter the epigenetic code through several mechanisms.…”
Section: Epigenetics As An Emerging Area Of Pollutant Toxicity Rmentioning
confidence: 99%
“…For example, we have demonstrated that exposure to coplanar PCBs, including PCB 77 and PCB126, can induce vascular endothelial cell dysfunction and inflammation through alterations in histone modifications of the p65 subunit of NF-kB that result in its increased activation (66). Additionally, we have shown that the commercial PCB mixture Aroclor 1260 can upregulate miRNAs associated with cardiac injury and inflammatory pathways in primary human endothelial cells (69). In humans, it has been observed that exposure to polyaromatic hydrocarbons (PAH) results in alterations in specific miRNAs associated with oxidative DNA damage and lipid peroxidation in coke oven workers (67).…”
Section: Epigenetics As An Emerging Area Of Pollutant Toxicity Rmentioning
confidence: 99%